National idea as a factor of society modernization: foreign and domestic experience (Journal of Philosophy Culture and Political Science, 2019)
The article analyzes the national idea as a system of common values, ideals, interests of the state, supported by all its citizens and inspiring them. The significance of the national idea is seen in its role to consolidate the entire population of the country into a single whole, to mobilize society to achieve strategic goals. The author investigates the conditionality of the uniqueness of the national idea by deep sociocultural grounds, first of all, traditional religion, beliefs, ethical norms, local traditions, customs, peculiarities of the people’s mentality, historical situation. In the work on the example of a number of countries, foreign experience in the formulation of a national idea based on religious, cultural and civilizational roots has been studied. We also studied domestic experience in understanding the national idea, both in the past and in the present. On the whole, the multifaceted positive role of the national idea in awakening public consciousness, strengthening national identity, reforming society and the state, their modernization and increasing competitiveness is shown.Key words: national idea, values, ideals, religion, modernization.